A pathway towards the development and evolution of consumer behavior: Policy directions for sustainable development and improvement of nutrition - Su, Fang; Chang, Jiangbo; Zhang, Xing; Fahad, Shah; Aslam, Shimza Bint (Frontiers in Nutrition, 2022)
'Information asymmetry' and 'information paradox' in the knowledge production and transaction process have caused extremely complicated problems in the consumer behavior and knowledge payment market. In this study, firstly we construct an evolutionary game model to analyze the development and evolution trends of economic complexity and technological innovation “use of technologies in improvement of utilization”. Secondly, this paper aims to explore the key factors affecting the development and evolution of the development of sustainable food systems in the perspectives of subsidy, punishment, cost, and benefit. Findings of this study reveal that: (1) In the online food trading market, the strategy of the seller, buyer and platform will be stable in six situations, and the "lemon problem" will emerge with the development and evolution of the online food trading market. (2) The strategy of each subject in the online food trading market will be affected by variables such as denoted by Cost difference between positive performance and negative performance of the seller, Punishment from the buyer with positive participation to the seller with negative performance, Subsidy from the platform with positive regulation to the seller with positive performance etc. and various factors are expected to affect the consumer behavior towards sustainable production. Based on our study findings, it is proposed that by constructing a complete and standardized system of online food trading market from the aspects of examination and verification institution, reward and punishment institution, and supervision institution, it will be it will be possible to uncover the direction in order to effectively improve the nutrition and sustainable food consumption.